RELIGIOUS VALUES AND CULTURAL LEARNING IN JAIPONG DANCE TRAINING AMONG SUNDANESE WOMEN - Fenty Sukmawaty; Siska Hestiana; Tanti Agustiani (Hikmah: Journal of Islamic Studies, 2026)
AbstractThis study examines how religious values and cultural learning are negotiated through Jaipong dance training among Sundanese women. It uses a descriptive qualitative approach within a cultural anthropological perspective. The data were drawn from the Jaipong Traditional Movement and Dance Training Program organized for members of the Dharma Wanita Persatuan (DWP) of the Sukabumi Regency Social Affairs Office, West Java. Ten Sundanese women participated in the program. Data were collected through participant observation, field notes, program documentation, activity reports, participant evaluation results, and participant interview data, then analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings show that participants interpreted Jaipong as a means of preserving Sundanese cultural heritage and strengthening cultural identity, social solidarity, discipline, mutual respect, and responsibility. The training also shows a negotiation between bodily expression in dance, Islamic ideas of modesty, and local cultural tradition. Rather than treating Jaipong training as explicit dakwah bil hal, this study reads the activity as a cultural learning process in which social values compatible with Islamic ethics are practiced through cooperation, mutual aid, and social cohesion. The study contributes to Islamic studies, cultural anthropology, and gender studies by explaining how Sundanese Muslim women negotiate religious values and cultural identity through embodied cultural learning. ABSTRAKPenelitian ini bertujuan mengkaji bagaimana nilai-nilai keagamaan dan pembelajaran budaya dinegosiasikan melalui pelatihan tari Jaipong pada perempuan Sunda. Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan perspektif antropologi budaya. Data diperoleh dari Program Pelatihan Gerak dan Tari Tradisional Jaipong yang diselenggarakan bagi anggota Dharma Wanita Persatuan (DWP) Dinas Sosial Kabupaten Sukabumi, Jawa Barat. Partisipan penelitian terdiri atas sepuluh perempuan Sunda. Data dikumpulkan melalui observasi partisipatif, catatan lapangan, dokumentasi program, laporan kegiatan, hasil evaluasi peserta, dan data wawancara peserta, kemudian dianalisis menggunakan model analisis interaktif Miles, Huberman, dan Saldaña. Hasil penelitian menunjukkan bahwa peserta memaknai tari Jaipong sebagai media pelestarian warisan budaya Sunda sekaligus sarana untuk memperkuat identitas budaya, solidaritas sosial, kedisiplinan, sikap saling menghormati, dan tanggung jawab. Pelatihan ini juga memperlihatkan proses negosiasi antara ekspresi tubuh dalam tari, konsep kesopanan menurut ajaran Islam, dan tradisi budaya lokal. Alih-alih dipahami sebagai bentuk eksplisit dakwah bil hal, praktik pelatihan tari Jaipong lebih tepat dibaca sebagai proses pembelajaran budaya yang memunculkan nilai sosial sejalan dengan perilaku etis, semangat tolong-menolong, dan penguatan kohesi sosial. Penelitian ini berkontribusi pada kajian Islam, antropologi budaya, dan studi gender dengan menjelaskan bagaimana perempuan Muslim Sunda menegosiasikan nilai-nilai keagamaan dan identitas budaya melalui pembelajaran budaya yang bersifat embodied dalam pelatihan tari Jaipong.